Effect of Environmental Factors on the Acute Respiratory Infection Incidence Among Toddlers - Shafira, Widya; Khasanah, Uswatun; basyir, Pahmi budiman saputra (Journal of Maternal and Child Health, 2023)
Background: Acute Respiratory Infection (ARI) is one of main public health problems found in Cirebon. Defining the factors governing this problem is crucial to reduce the burden of the disease. This study aims to analyze the effect of environmental factors on the incidence of ARI in toddlers in the territory of Gempol Community Health Center of Cirebon district. Subjects and Method: This was a cross sectional study conducted at Gempol Community Health Center, Cirebon district, West Java, Indonesia. A total of 97 subjects were surveyed using questionnaire and direct measurement based on the Lemeshow formula. Independent variables taken into account were air pollution, exposure to cigarette smoke, air ventilation at subjects’ house, humidity inside the house, and occupant density. Data were analyzed by Chi-Square test and Logistic Regression test. Results: Multivariate results showed that air population (OR= 4.72; 95% CI= 1.65 to 13.46; p = 0.004); humidity in the house (OR= 8.95; 95% CI= 3.06 to 26.13; p = 0.001); humidity in the house (OR= 3.38; 95% CI= 1.15 to 9.87; p = 0.026) increased with the the acute respiratory infection incidence among toddlers, and there were statistically significant. Conclusion: House humidity is the most significant factor governing the incidence of ARI in the territory of Gempol Community Health Center of Cirebon District. Keywords: acute respiratory infection, toddler, environmental factors. Correspondence: Uswatun Khasanah. Faculty of Medicine, Universitas Swadaya Gunung Jati. Taman pemuda 1A, Sunyaragi, Kesambi Sub District, Cirebon 45132, West Java, Indonesia. Email: uswatunhasanah7@gmail.com. Mobile +6281320001650.